Motives influencing the co-production behavior of Vietnamese tourists: Scale development and validation - Dao, Truong Thi Xuan (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
The study highlights a number of incentives that impact product co-production behavior, including: economic, psychological, and social motivations. It was developed from the research framework "Descriptive model of the consumer co-production process" by M. Etgar. Nevertheless, particularly for travel-related goods, defined measurement scales for these variables are still lacking. A credible and dependable scale measuring the social, psychological, and economic factors influencing co-production behavior through a conceptual approach is needed to close this study gap. Multidimensional ideas become essential and significant. From an operational standpoint, tourist managers can assess or track the success of co-production techniques using measuring scales as a reference. The main purpose of this research is to develop a measurement scale for the group of psychological motives, economic motives and social motives that influence tourists’ co-production behavior. With this goal, the techniques implemented for measuring these concepts will follow the guidelines (Churchill, 1979) of including the following steps: 1) Identify topics and create categories; 2) Screening and correction; and 3) Validate the scale.